STRATEGY OF RUMAH BACA CAHAYA INSPIRASI (RUBACI) IN CULTIVATING READING AMONG COASTAL CHILDREN - Syafirah, Ulfa; Sumanti, Solihah Titin; Yusniah, Yusniah (PERSPEKTIF: Journal of Social and Library Science, 2023)
The purpose of this study is to describe the Strategies of the Cahaya Inspiration Reading House in cultivating reading among coastal children. describes what obstacles are faced in cultivating reading in coastal children's grief and describes the solutions taken to overcome the obstacles encountered in increasing a reading culture. This research uses a qualitative approach with descriptive methods. The research location is the Light of Inspiration reading house (RUBACI) which is in the village of Bandar Sono, Nibung Hankus sub-district, Batubara district. Data was collected through observation, interviews and documentation. The data analysis technique used in this research is data reduction, data display and data retrieval. Data validity tester. The results of this study concluded that the light inspiring reading house is making maximum efforts to improve the reading culture among children even though there are still many obstacles to be faced, but the management of the light inspiration reading house has made several solutions to overcome the obstacles it faces. Suggestions for the manager of the light-inspired reading house include managers who are expected to be more active in managing the reading house and need to improve and add several facilities such as bookshelves.